2016
DOI: 10.1590/1981-22562016019.160043
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the institutionalization of the elderly: a case-control study

Abstract: Objective: to identify the factors associated with the institutionalization of the elderly. Method: a case-control, population-based study was performed with 387 elderly people. The study considered cases of elderly people (n=191) living in long-term care facilities, and a control group (n=196) who lived in homes in urban areas of the city. Both groups were identified from the records of the Family Health Strategy and were randomly selected. Institutionalization was considered a dependent variable, and sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0
30

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 27 publications
5
27
0
30
Order By: Relevance
“…2019;40:e20180377 of the aged and their dependence to perform activities of daily living as limiting the care at home. This finding corroborates other national and international studies in which the aged with physical disabilities, dependence to perform basic activities of daily living and presence of chronic diseases were more likely to be institutionalized (17)(18)(19) . In addition to the intensity of care, the home structure was reported by the adult child caregivers as a factor that hinders care, making them consider the institutionalization of their parents, also identified in another study (18) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2019;40:e20180377 of the aged and their dependence to perform activities of daily living as limiting the care at home. This finding corroborates other national and international studies in which the aged with physical disabilities, dependence to perform basic activities of daily living and presence of chronic diseases were more likely to be institutionalized (17)(18)(19) . In addition to the intensity of care, the home structure was reported by the adult child caregivers as a factor that hinders care, making them consider the institutionalization of their parents, also identified in another study (18) .…”
Section: Discussionsupporting
confidence: 91%
“…Related to the limitations of daily life, adult child caregivers also reported, as a reason for institutionalization, the occurrence of diseases that impair the cognitive ability of their parents, among which highlighted diseases such as Alzheimer's, Parkinson's and others. This finding is like that found in national and international studies, which identified that the cognitive impairment of the aged is associated with their institutionalization (17,19) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, the institutionalization of the elderly should be the last alternative care which is worrying, as the Home for Elderly People is occupying a different place from the one that would be due. 7 Comparing the found in relation to the dimensions and the structure of the external space with the one determined by the RDC from the ANVISA No. 283/2005 some inadequacies were identified because, it establishes external access with at least two doors, Being an exclusively of service, with a free span with minimum width of 1.10 m, with simple locking without the use of locks or keys.…”
Section: Resultsmentioning
confidence: 99%
“…Observa-se, na literatura sobre o tema, estudos relacionados aos residentes da ILPIs em sua maioria (Silva, Dias, & Piazza, 2017;Scarabottolo, et al, 2017;Hartmann Junior, & Gomes, 2017;Lini, Portella, & Doring, 2016), concentrando-se em aspectos médicos e clínicos dos idosos e frequentemente com discussões sobre as demandas assistenciais (Roquete, Batista, & Arantes, 2017 delineamento das pesquisas, incluindo-se: 1) Delineamento das publicações; 2) perfil dos participantes dos estudos; 3) instrumentos utilizados para coleta dos dados; 4) área de conhecimento dos autores; e 5) principais temáticas abordadas.…”
unclassified